The Effectiveness of Ergonomic Chairs on Traditional Silk Weaving Craftsman in Polewali Mandar District, West Sulawesi - Atjo Wahyu; Andi Ummu Salmah; Muhammad Syafar; Muhammad Ashar; Iva Hardi Yanti (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objectives: This research examines the effectiveness of providing interventions in the form of ergonomic chairs in increasing productivity and reducing work fatigue, and the risk of musculoskeletal disorders in silk weavers in Polman Regency, so that it can provide information for policy makers in formulating optimal health management for workers, especially in the sector. informal or small scale. Methods: This research used a quasi-experimental design on silk weaving craftsmen in Polewali Mandar Regency, West Sulawesi, to evaluate work fatigue, productivity, work resilience, and musculoskeletal risk through a subjective assessment scale. Research subjects were selected using a purposive sampling method, involving 20 craftsmen (10 treatment groups and 10 control groups). Data was collected through direct observation and structured interviews, and pre-tests and post-tests were carried out to evaluate changes before and after the intervention. Data analysis used the Wilcoxon and Mann-Whitney tests to test significant differences. Results: The results of statistical analysis show that the intervention is effective in reducing fatigue levels p=0.002, risk of musculoskeletal disorders p=0.000, and shortening production time for silk weavers in producing silk woven sarongs p=0.001. The length of the weaving results shows a p value of 0.146 which indicates there is no statistically significant difference between the intervention group and the control group in terms of the length of weaving produced in a week. However, the observation results showed that the average weaving results in the intervention group remained higher than those in the control group. Conclusions: The main results prove that the intervention is effective in reducing fatigue levels, the risk of musculoskeletal disorders, and shortening production time for silk weaving.